Is the African Union’s decision on the ICC and the adoption of Article 46A Bis of the Protocol on Amendments to the Protocol on the Statute of the African Court of Justice and Human rights unlawful under international law? - Amadhila, Nelago Ndapandula (Department of Public Law, 2015)
Includes bibliographical references.